Ekosistem Keuangan Syariah Pada Islamic Microfinance Instittutions Dengan Philantropy Ekonomi Islam Di Pesisir Utara Jawa: (Studi Kasus 6 Koperasi Syariah di Pesisir Utara Lamongan) - Latifah, Eny (MADINAH, 2022)
The purpose of this study was to determine what ecosystems exist in Islamic Microfinance Institutions. This research method uses descriptive qualitative using data processing to the maximum in 6 (Six) Islamic cooperatives in the North Coast of Lamongan. Analysis of existing data is the result of processing sourced from triangulation of data in the form of observations, interviews and documentation in order to produce real data. The results showed that the ecosystem in the Islamic Microfinance Institutions consists of Islamic Economic Phylanthropic Instruments including Waqf, Zakat, Infaq, and Shodaqoh. Other ecosystems include providing innovations in sharia financial products that can truly fulfill and increase financial inclusion in the North Coast of Lamongan.